Field notes contributed by Fred Lesher, spring 1996 - Lesher, Fredet al (1996)
Spring report of birds and locations contributed by Fred Lesher. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed/flatbed